Financial Crisis and Migrant Domestic Workers in Spain: Employment Opportunities and Conditions during the Great Recession. Issue 4 (December 2019) - Hellgren, Zenia; Serrano, Inmaculada
This article explores the impact of the Great Recession on migrant domestic workers in Spain. We argue that the domestic service sector's relative resistance to job destruction has transformed it to some extent into a refuge activity for unemployed women from other sectors, both migrants and native Spanish workers. This leads to intensified competition over jobs and increasing stratification among domestic workers, with serious consequences both for migrant women's opportunities to make a living in Spain and for their migration projects at an international level. Based on 90 in-depth interviews with female migrant domestic workers and stakeholders, we find that this group of workers has been seriously affected by unemployment, underemployment, and worsened job conditions. As a consequence, new and already settled migrants find the chances to gain their livelihood in Spain substantially reduced, and many of those who migrated in order to support the family back home through remittances, or to save some money and eventually return, are at present unable to do so.